PROFIL PENYELESAIAN SOAL KEDUDUKAN DUA GARIS DALAM BIDANG DATAR SISWA KELAS VIII SMP NEGERI 4 SIGI: Profile of Solving the Position of Two Lines in a Flat Plane For Class VIII Stident of SMP Negeri 4 Sigi - Ananda, Sinar; Bennu, Sudarman; Hasbi, Muh. (Universitas Tadulako, 2023)
This study aims to obtain a description of the problem solving for the position of two lines in a flat plane for class VIII students of SMP Negeri 4 Sigi. This type of research is descriptive research with a qualitative approach. The subjects of this study were selected based on the results of the odd semester report cards for class VIII A students. The subjects used in this study were students, namely one student each with high and low a mathematical abilities. The results of this study indicate that: (1) Completion of students with high mathematical abilities in solving parallel line problems, namely determining the coordinate points on both lines and using the gradient formula of the line. Then connect the gradient value of the line obtained with the condition that the two lines are parallel. After that, show the image of the two parallel lines. (2) Completion of students with high mathematical abilities in solving perpendicular line problems, namely determining the coordinate points on both lines and using the gradient formula of the line. Then connect the gradient value of the line obtained with the condition that the two lines are mutually perpendicular. After that, show the image of two lines that are perpendicular to each other. (3) Completion of low math ability students in solving parallel line problems, namely determining the coordinate points on both lines and using the gradient formula of the line. (4) Completion of students with low a mathematical ability in solving perpendicular line problems by determining coordinate points on both lines and using the gradient formula of the line.